How Can Collaborative Work Shape the Evolution of a Project Management Teaching Tool? - Boeira, Matheus; Muller, Dionas; Neves, Raul; Araújo, Thiago; Bernardino, Maicon (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248575, 2026)
Research Context: Project Management (PM) is essential in Software Engineering (SE) education, requiring technical and collaborative skills. Effective tools must incorporate modern PM methodologies to address evolving educational needs. Practical Problem: Existing tools lack features such as real-time collaboration, integration of updated PM principles, and adaptability, limiting their ability to develop comprehensive PM skills among students. Proposed Solution: This study enhances a collaborative web-based IS for PM education, integrating the 6th and 7th editions of the PMBOK®. New features, including a real-time collaborative editor and hybrid project management approaches, were implemented to improve learning outcomes. Related IS Theory: Using the 3C model (Communication, Coordination, Cooperation), the tool was designed to facilitate effective collaboration and align with established collaborative frameworks in IS research. Research Method: We employed an user-centered development, with surveys and iterative testing guiding enhancements. Modern technologies, such as React and Yjs, enabled real-time functionalities. The tool’s usability and functionality were evaluated through user feedback. Summary of Results: The enhanced tool supports real-time collaboration, advanced document editing, and hybrid PM practices, addressing previous limitations. It serves as a practical example of applying IS frameworks to PM education. Contributions and Impact to IS Area: This study demonstrates how IS can transform PM education through collaborative systems and agile methodologies, aligning tools with both academic and industry needs. Future work includes case studies to further validate the tool’s impact.